Allometric relationships and carbon content for biomass-carbon estimation of East African Highland Bananas (Musa spp. AAA-EAHB) cv. Kibuzi, Nakitembe, Enyeru and Nakinyika - Kamusingize, Daphine; Mwanjalolo Majaliwa, Jackson; Komutunga, Everline; Tumwebaze, Susan; Nowakunda, Kephas; Namanya, Priver; Kubiriba, Jerome (African Journal of Agricultural Research, 2018)
Globally, interests to increase carbon stocks have gained momentum in both woody and non-woody ecosystems. Despite efforts made to generate appropriate methods to estimate these stocks, most equations developed do not cater for intraspecific variabilities across e.g. species, regions or growth stages; especially in the case of bananas. Therefore, there is need to develop more robust equations to improve on the precision of biomass-carbon prediction especially at local scales to facilitate estimation of specific carbon stocks often lost in global assessments. This study aimed at developing cultivarspecific biomass estimation relationships and determining carbon content of EAHB cultivars at two growth stages. Plant data were collected purposively using destructive sampling techniques on farmers’ plots for 4 cultivars (Kibuzi, Nakitembe, Enyeru and Nakinyika) in two agro-ecological zones: the L. Victoria crescent and the South-western farmlands in the districts of Lwengo and Mbarara respectively. Results show that biomass differed across cultivars (P<0.001); hence four equations (Enyeru, Nakinyika, Kibuzi_Nakitembe and Generic) were developed following an exponential function, y=Aexp(ax), using diameter at breast height (DBH) as the predictor variable with an R2 range of 82-94%. EAHB mean carbon content varied significantly with growth stage (P<0.05) (47.6% for maiden plants before flowering and 48.8% for mature plants with a developed bunch). This study concludes that it is important to develop cultivar-specific equations for biomass-carbon estimation of EAHB cultivars to help assess their contribution to the carbon cycle especially in future studies.
Keywords: East African Highland Bananas (EAHB) cultivars; Allometric equations; Total plant biomass; Carbon content; Growth stage